2017
DOI: 10.1111/acer.13493
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Role of Alcohol Use in Adolescent Externalizing and Internalizing Problems: A Mendelian Randomization Study

Abstract: The results suggest that alcohol use is a cause of adolescent aggression and attention problems but not adolescent delinquency, anxiety, or depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…A genetic correlation can reflect a causal relationship (Gage, Smith, Ware, Flint, & Munafò, 2016), but for environmentally influenced disorders one would expect also to find an environmental correlation in the same direction. Previous twin studies have failed to find an environmental association (Nelson et al, 2000;Tambs et al, 1997), and the lack of effects from AUD to anxiety is also in line with a previous Mendelian randomization study (Chao et al, 2017). The model that included a small and negative environmental path from AUD to other anxiety disorders had slightly better fit than the model with only the genetic path.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…A genetic correlation can reflect a causal relationship (Gage, Smith, Ware, Flint, & Munafò, 2016), but for environmentally influenced disorders one would expect also to find an environmental correlation in the same direction. Previous twin studies have failed to find an environmental association (Nelson et al, 2000;Tambs et al, 1997), and the lack of effects from AUD to anxiety is also in line with a previous Mendelian randomization study (Chao et al, 2017). The model that included a small and negative environmental path from AUD to other anxiety disorders had slightly better fit than the model with only the genetic path.…”
Section: Discussionsupporting
confidence: 78%
“…This could be true also for SAD. On the other hand, a Mendelian randomization study found alcohol use not to cause symptoms of anxiety (Chao, Li, & McGue, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, one MR study found evidence for a causal effect of alcohol use on attention problems and aggression in adolescents (but not on delinquency, anxiety, or depression) 30 . Two other studies provided evidence that genetic liability to ADHD, as well as higher extraversion, has a causal effect on smoking initiation 31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…Early use of alcohol during adolescence is an important risk factor for alcohol‐related problems (ARP) including blackouts (Marino and Fromme, ) as well as several internalizing and externalizing problems (Chao et al., ). Although several studies have explored different facets of impulsivity and its relationship with adolescent drinking, many questions about this relationship remain unanswered (Peeters et al., ).…”
mentioning
confidence: 99%